PENGARUH PENYELESAIAN SENGKETA ARBITRASE TERHADAP KEPASTIAN HUKUM PERSEROAN - Ervawati; Pandri Zulfikar; Dede Agus Sodikin; Djamal Efendi; Imam Fathwa (CV. Lafadz Jaya, 2026)
Dispute resolution is a fundamental aspect of legal practice, particularly in the business and corporate context. Arbitration, as one of the mechanisms for dispute resolution outside the ordinary courts, has provided a significant alternative for business entities, including limited liability companies. This study aims to analyse the impact of dispute resolution through arbitration on legal certainty for companies in Indonesia. The research method employed is a normative legal approach, utilising legislative and conceptual frameworks. The findings indicate that arbitration makes a positive contribution to legal certainty for limited liability companies through the final and binding nature of its awards, the efficiency of dispute resolution timelines, and the protection of business confidentiality. However, there are several obstacles affecting the optimisation of arbitration’s function, including legal uncertainty regarding the enforcement of arbitral awards, limitations on the scope of disputes that can be resolved through arbitration, and the relatively high costs of arbitration. Based on the results of the analysis, this study recommends the need to revise Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution to provide more comprehensive legal protection for companies.